Urban vegetation benefits in mediterranean cities for climate change adaptation and water usage efficiency – a case study in Algarve, Portugal - Pedro Matias; Pedro Matias; Pedro Matias; Manuela Moreira da Silva; Manuela Moreira da Silva; Manuela Moreira da Silva; João Teigão; Amílcar Duarte; Amílcar Duarte (Frontiers in Environmental Science)
In the current climate change scenario, Mediterranean cities face heatwaves and reduced availability of freshwater alternated with intense precipitation events in short periods. The demand for water, especially for urban and tourism purposes, is rising, particularly in coastal cities. The importance of integrating nature into cities, particularly trees, has been studied for its benefits in adapting to climate change and improving quality of life. However, water scarcity in cities remains a limiting factor for ensuring the water needs of urban trees and, consequently, the ecosystem services they provide. In this study, we quantified the ecosystem services (CO2 sequestration and storage, O2 production, air pollutants removal, and hydrological effects as transpiration, water intercepted and avoided runoff) provided by urban vegetation in Faro (Algarve, Portugal), with a detailed analysis of three green spaces. We analyzed the importance given to green spaces and the community preferences. Rainwater harvesting was studied as an alternative water source for irrigation and its advantages for the urban water cycle. We found that urban vegetation across the city sequesters 1.09 × 103 t. yr−1 CO2, stores 4.01 × 103 t C, contributes to air pollutant removal (CO = 114; O3 = 3.56 × 103; NO2 = 313; SO2 = 224; PM10 = 872; PM2.5 = 70) kg. yr−1, and prevents 861 m3. yr−1 of surface runoff. In general, people inquired use to visit and value the city’s green spaces, enjoy activities in nature, have definite preferences regarding green spaces, and are available to suggest actions to improve these spaces. It was confirmed that in order to maintain urban green spaces and the ecosystem services that their vegetation provides to the community, rainwater harvesting is of utmost relevance representing a reduction in drinking water for irrigation of 4.20 × 103 m3. yr−1 in the three studied green spaces.